Peritonite esclerosante encapsulante pós-diálise peritoneal - Cestari, Alexandre Tagliari (2013)
Patients with chronic renal failure in use of peritoneal dialysis (PD) are subject to various complications of the renal replacement therapy. We report a rare complication of PD in which the peritoneum, after years of contact with hypertonic dialysate, is gradually replaced by fibrous tissue. This patient had several complications after initiation of PD including a bacterial peritonitis, tertiary hyperparathyroidism (being treated with parathyroidectomy 2) and cholelithiasis (being treated with laparoscopic cholecystectomy). After 8 years of peritoneal dialysis was transferred to hemodialysis by decreasing ultrafiltration and episodes of intestinal sub-occlusion, being diagnosed as sclerosing encapsulating peritonitis (SEP). He is currently on corticotherapy with a significant reduction of symptoms and likely stabilization of the SEP.